Deleuze and Psychoanalysis : Philosophical Essays on Deleuze's Debate with Psychoanalysis - De Bolle, Leen (Book collections on Project MUSE., 2010)
Gilles Deleuze is among the twentieth century's most important philosophers of difference. Reading and appreciating his work requires an unusual degree of openness and willingness to enter a complicated but extremely rich system of thought. His oeuvre is marked by abundant debates with and references to a variety of authors of many different domains, the sophisticated conceptual framework, the creation of new concepts, and the injection of existing concepts with new meanings. Deleuze and Psychoanalysis is both a guide to reading Deleuze and a direct confrontation with issues at stake in his work, particularly the debate with and against psychoanalysis. This debate not only offers the occasion to find an entrance to Deleuze's basic thought but also throws the reader into the middle of the dispute. Offering different points of view, the authors of this book provide a clear and perspicuous overview of subject matter of interest to all psychoanalysts, Deleuzean or otherwise.